2022
DOI: 10.1039/d2ta00406b
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature Li–S battery enabled by CoFe bimetallic catalysts

Abstract: Lithium-sulfur (Li-S) batteries are considered to be a promising energy storage device. To ensure practical applications at natural environment, Li-S batteries must be capable of performing normally at low temperature....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 70 publications
(84 reference statements)
0
22
0
Order By: Relevance
“…The decreased temperature would also weaken the solid ionic diffusivity within the bulk electrode materials. [ 8,74 ] The sluggish ion transport kinetics would hamper the access of ions into the active sites in the matrix of electrode materials, suffering a severe capacity decline of low‐temperature batteries. [ 75 ] Therefore, the electrochemical behaviors of electrodes depend significantly on the structural properties of electrode materials.…”
Section: Strategies For Promoting Low‐temperature Ion Transportmentioning
confidence: 99%
“…The decreased temperature would also weaken the solid ionic diffusivity within the bulk electrode materials. [ 8,74 ] The sluggish ion transport kinetics would hamper the access of ions into the active sites in the matrix of electrode materials, suffering a severe capacity decline of low‐temperature batteries. [ 75 ] Therefore, the electrochemical behaviors of electrodes depend significantly on the structural properties of electrode materials.…”
Section: Strategies For Promoting Low‐temperature Ion Transportmentioning
confidence: 99%
“…3d), there are spin–orbit dipoles of Co 2p 3/2 and Co 2p 1/2 , and two satellite peaks. 39 Two peaks with binding energies centered at 778.5 and 794.9 eV are attributed to Co 3+ , and the two peaks centered at 781.2 and 798.1 eV are assigned to Co 2+ . Two satellite peaks are located at 787.6 and 800.1 eV, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Besides, Gao et al designed a freestanding 3D porous-carbon-film-embedded CoFe alloy nanoparticle. [193] They demonstrated that CoFe alloys worked as efficient catalyst for fast polysulfide conversion, enabling Li-S batteries with an enhanced capacity of 836 mAh g −1 at 0.2 C with a capacity retention rate of 94.5% after 100 cycles at a low temperature of −20 °C.…”
Section: Alloysmentioning
confidence: 99%